2017
DOI: 10.1186/s13018-017-0595-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between knee osteoarthritis and meniscal shape in observation of Japanese patients by using magnetic resonance imaging

Abstract: BackgroundThe aims of this study were to reveal the characteristics of the meniscal shape at each knee osteoarthritis (OA) severity level and to predict trends or patterns of the meniscal shape change as associated with knee OA progression.MethodsFifty-one patients diagnosed with knee OA based on X-ray and magnetic resonance (MR) images were evaluated. They were divided into three groups based on the Kellgren–Lawrence (KL) grade: normal group (KL grade of 0 or 1), mild group (KL grade of 2 or 3), and severe gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
3
9
1
Order By: Relevance
“…This fact suggested that the change of MPH was less closely associated with OA-related knee structural abnormalities when compared with medial meniscal body height. A recent study by Kawahara et al reported a statistically significant association between MPH and cartilage lesions, which conflicted with our findings [24]. A possible reason was that their results did not adjust for the common confounders such as meniscal lesions.…”
Section: Discussioncontrasting
confidence: 99%
“…This fact suggested that the change of MPH was less closely associated with OA-related knee structural abnormalities when compared with medial meniscal body height. A recent study by Kawahara et al reported a statistically significant association between MPH and cartilage lesions, which conflicted with our findings [24]. A possible reason was that their results did not adjust for the common confounders such as meniscal lesions.…”
Section: Discussioncontrasting
confidence: 99%
“…Two orthopaedic surgeons, with more than 10 years of experience in reading radiographs, who were blinded to the OA grade at radiography and clinical data, systematically evaluated the presence of MME as previously reported [24]. Briefly, the ends of the tibia and meniscal edge were manually identified from an MR coronal slice, and the horizontal distance between them was defined as the amount of meniscus extrusion.…”
Section: Mr Image Interpretationmentioning
confidence: 99%
“…[17] , [7] , [18] Several MRI studies evaluating early OA changes in meniscal morphology and cartilage degeneration have been published. [19] , [20] To the best of our knowledge, there has been no study comparing MOAKS pre-and post-ACLR. In this study, early knee OA was easily quanti ed using MOAKS in ACL-injured knees .…”
Section: Discussionmentioning
confidence: 99%